Environment and production technology division (EPTD) - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
The Environment and Production Technology Division (EPTD) of the International Food Policy Research Institute identifies ways to combine appropriate and affordable food and agricultural technologies with supportive policies, institutions, and investments. With a research and outreach focus on global change, natural resource management, spatial data, and science policy, EPTD contributes to three of the strategic research areas in IFPRI’s 2018– 2020 Strategy: (1) fostering a climate-resilient and sustainable food supply, (2) transforming agricultural and rural economies, and (3) strengthening institutions and governance.